PHILOSPHICAL FOUNDATION IN ENGLISH EDUCATION CURRICULUM RENEWAL BASED ON INDONESIAN QUALIFICATION FRAMEWORK (KKNI) - Ima Isnaini Taufiqur Rohmah (IKIP PGRI Bojonegoro, 2017)
Abstract: Philosphical Foundation in English Education Curriculum Renewal Based on Indonesian Qualification Framework (KKNI). Indonesian Qualification Framework (IQF) is a description of qualification levels for all Indonesian learning outcomes or certificate statements in Indonesian schooling from year 9 to higher education. The IQF holds a legal endorsement in the form of Presidential Decree no. 8/2012. This IQF will specify equivalencies between Indonesian and foreign qualifications, thus improving Indonesia’s international competitiveness and making the country more open to global trade. As a consequence, the structures of curriculum in all Indonesian educations should base on this document. English teacher Education needs English language teacher education with appropriate structures of curriculum relevant to the global world and 21st century learning. This article intends to describe the IQF, and the philosophical foundation structure of the EL Teacher education Curriculum in Indonesia.Keywords: Curriculum, Renewal, Indonesian Qualification Framework. and English Language Teacher EducationAbstract: Landasan Filosofis dalam Perbaruan Kurikulum Pendidikan Bahasa Inggris Berdasarkan Kerangka Kualifikasi Nasional Indonesia. Kerangka Kualifikasi nasional Indonesia (KKNI) adalh sebuah pejabaran level kualifikasi tujuan pembelajaran di Indonesia atau sebagai sebuah pernyataan tertulis sekolah di Indonseia dari mulai kelas 9 sampai denagn pendidikan tinggi. KKNI merupakan mempunyai aturan tegas yang termuat dalam Peraturan Presiden No. 8/2012. KKNI akan lebih memspesifikkan kesaamaan antara kualifikasi luar negeri dan kualifikasi pendidikan di Indonesia, untuk meningkatkan daya saing Indonesia dimata internasional dan membuat negara kita lebih terbuka dengan pasar bebas. Sebagai konsekuensinya, stuktur kurikulum di semua level pendidikan di Indonesia haru berdasarkan dokumen ini. Pendidikan Guru Bahasa Inggris membutuhkan kurikulum pendidikan guru Bahasa Inggris yang memiliki struktur kurikulum yang tepat dan relevan terhadap globalisasi dan pembelajaran pada abad 21. Artikel ini bertujuan untuk mendeskripsikan kurikulum Pendidikan Guru Bahasa Inggris dan landasan filosofis kurikulum pendidikan Guru Bahasa Inggris di Indonesia.Kata kunci: Kurikulum, Perubahan kurikulum, KKNI, Pendidikan Guru Bahasa inggris.